Tables of Racah coefficients - Nikiforov, A. F.; Uvarov, V. B. (Vasilii Borisovich); Levitan, IU. L. (Mathematical tables series ;, 1965)
Tables of Racah Coefficients presents a compilation of tables of Racah coefficients. Racah coefficients appear and are widely used in a number of problems in quantum mechanics; in the theory of spectra of complex atoms and nuclei; in the theory of angular distributions of nuclear reactions; in the theory of angular correlations of decay particles; and many other problems where the sums of products of three or more Clebsch-Gordan coefficients occur.